The Soviet Writers' Union and Its Leaders : Identity and Authority under Stalin - Any, Carol Joyce, 1952- (Studies in Russian literature and theory, 2020)
"This book argues that Stalin chose Writers' Union leaders, such as Maxim Gorky and Alexandr Fadeyev, whose psychologies he could exploit. He ensured their loyalty with material benefits but also with a philosophical argument calculated to assuage their moral qualms about supporting the regime"--